Depletion of serotonin decreases the effects of the kappa-opioid receptor agonist U-69593 on cocaine-stimulated activity - Zakharova, Elena; Collins, Stephanie L.; Åberg, Maria; Kumar, Adarsh; Fernandez, J.B.; Izenwasser, Sari (European journal of pharmacology, 2008)
Treatment with a kappa-opioid receptor agonist for 5 days decreases locomotor activity and reduces activity in response to a cocaine challenge 3 days later. In addition, chronic cocaine increases kappa-opioid receptor density, striatal dynorphin, and dynorphin gene expression in the striatum. The upregulation of kappa-opioid receptors after cocaine treatment occurs predominantly in brain regions that are highly innervated by serotonin. To determine if serotonin plays a role in the effects of kappa-opioid receptor agonists on cocaine-stimulated activity, parachloroamphetamine (PCA), which depleted serotonin by 53%–66%, or saline, was given prior to a five-day treatment with U-69593 or vehicle. Three days later each rat received a single injection of cocaine and locomotor activity was measured. Treatment with PCA had no effect on the ability of U-69593 alone to decrease locomotor activity. Thus, the behavioral effects of U-69593 alone were not dependent upon serotonin. In rats pretreated with saline, U-69593 treatment significantly blocked the locomotor-activating effects of cocaine. Following PCA pretreatment, however, there were no significant differences in locomotor activity in rats challenged with an injection of cocaine after treatment with U-69593 or vehicle. Thus, serotonin depletion prevented the long-lasting blockade of the locomotor-activating effects of cocaine subsequent to repeated administration of U-69593 but did not alter the effects of cocaine in rats that were treated with vehicle. Thus, the effects of PCA on U-69593 are not due to non-specific alterations in cocaine-induced locomotor activity. These findings suggest that serotonin plays an important role in mediating the effects of kappa-opioid receptor agonists on the behavioral response to cocaine.